Students' Attitudes Toward College Drinking: A Moral Intuitionist Approach. Issue 8 (2nd August 2020) - Silver, Eric
ABSTRACT: This study uses Moral Foundations Theory to examine the association between moral intuitions and college students' attitudes toward drinking. The data consist of 1, 447 college students sampled in 2017 at a large public university. Results show that students' attitudes toward drinking are associated with their moral intuitions. Specifically, students whose moral intuitions emphasize purity are less favorable toward drinking, while students whose moral intuitions emphasize group loyalty are more favorable. Results also show that these moral intuitions are mediated by religiosity and (to a lesser extent) involvement in Greek life, respectively. The study suggests the importance of extending the conception of morality beyond individual-oriented concerns with harm and fairness to include group-oriented concerns with purity and loyalty.